Hydrogen Commonly Applicable from Medicine to Agriculture: From Molecular Mechanisms to the Field - Li, Longna; Lou, Wang; Kong, Lingshuai; Shen, Wenbiao (Current Pharmaceutical Design, 2021)
The emerging field of hydrogen biology has to date mainly been applied in medicine. However, hydrogen biology can also enable positive outcomes in agriculture. Agriculture faces significant challenges resulting from a growing population, climate change, natural disasters, environmental pollution, and food safety issues. In fact, hydrogen agriculture is a practical application of hydrogen biology, which may assist in addressing many of these challenges. It has been demonstrated that hydrogen gas (H2) may enhance plant tolerance towards abiotic and biotic stresses, regulate plant growth and development, increase nutritional values, prolong the shelf life, and decrease the nitrite accumulation during the storage of vegetables, as well as increase the resilience of livestock to pathogens. Our field trials show that H2 may have a promising potential to increase yield and improve the quality of agricultural products. This review aims to elucidate mechanisms for a novel agricultural application of H2 in China. Future development of hydrogen agriculture is proposed as well. Obviously, hydrogen agriculture belongs to a low carbon economy, and has great potential to provide “safe, tasty, healthy, and high-yield” agricultural products so that it may improve the sustainability of agriculture.
Keywords: low-carbon agriculture